Religious Movements and the Adoption of New Media: The Internet Used by Hizbut Tahrir Indonesia After Disbanded - Dulkiah, Moh.; Setia, Paelani; Rosele, Muhammad Ikhlas (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2023)
This paper aims to examine the religious movement of Hizbut Tahrir Indonesia (HTI) when adopting new media in its movement activities in Indonesia. The research in this paper uses a qualitative method with data collection through online observation of the HTI website, Media Umat www.mediaumat.id. This research found that HTI as a religious movement also adopted the internet in its movement activities just like other religious movements, namely NU and Muhammadiyah. HTI's use of the internet also refutes the argument that the internet is incompatible with religion, which is based more on secularization arguments. The internet in fact provides new opportunities that are positively welcomed by the religious community, which makes it part of its culture according to its needs and interests. This religious response can be seen in HTI's use of the internet which can be categorized into three forms: ideological, polemical and contextual. All these forms of internet use show the positive impact of the internet for religion and the ability of religion to become part of modernity for its interests and needs by adapting the internet as a product of modernity.